English as a Lingua Franca in Digital Communication: A Systematic Review of Benefits and Challenges in Asian Contexts - Estera, Jennifer Claire; Danggol , Olive; Alinso, Jersy; Kege-e, Jesa; Pelila, John Rey (Papanda Publisher, 2026)
English has become a global language, facilitating communication across diverse linguistic and cultural contexts, particularly in digital spaces such as social media, messaging apps, and online learning platforms, where users often combine languages and cultural elements to construct and express their identities. This study aimed to systematically review the literature on English as a Lingua Franca (ELF) in digital communication to examine its advantages and challenges for learners and educators. A Systematic Literature Review (SLR) was conducted across ERIC, Taylor & Francis, and Cambridge Core, applying inclusion criteria for peer-reviewed, full-text studies published between 2021 and 2025 in Asia. Using a PRISMA flowchart, 161,121 records were initially identified and subsequently narrowed down to 29 relevant studies through a combination of automated and manual screening. Deductive thematic analysis categorized findings into advantages and disadvantages of digital ELF. Results indicate that digital ELF enhances language skills, speaking confidence, creativity, intercultural communication, autonomy, and learner motivation, but challenges remain, including unequal access to technology, limited teacher readiness, anxiety, and potential misunderstandings in intercultural interactions. It is concluded that digital ELF offers substantial opportunities for self-paced learning, identity expression, and intercultural engagement; however, its effectiveness depends on equitable access, supportive teachers, and the guided use of digital tools to ensure inclusive and meaningful participation.